2022
DOI: 10.1155/2022/3481102
|View full text |Cite
|
Sign up to set email alerts
|

MAO-B Polymorphism Associated with Progression in a Chinese Parkinson’s Disease Cohort but Not in the PPMI Cohort

Abstract: Introduction Genetic factors play an important role in Parkinson's disease (PD) risk. However, the genetic contribution to progression in Chinese PD patients has rarely been studied. This study investigated genetic associations with progression based on 30 PD risk loci common in a longitudinal cohort of Chinese PD patients and the Parkinson's Progression Markers Initiative (PPMI) cohort. Methods PD patients from the true world (TW) Chinese PD longitudinal cohort and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In addition to dopamine, MAO-B also degrades norepinephrine, which is implicated in several physiological functions, including cognition, pain, sleep, and emotional processing. Hence, MAO-B could mediate the pathophysiological mechanisms underlying the non-motor symptoms in PD, such as depression [ 8 ]. Recently, a study of PD patients from China and the Parkinson’s Progression Markers Initiative (PPMI) cohort has indicated that although the MAOB rs1799836 polymorphism was linked to the progression of non-motor symptoms of the patients in general in the Chinese cohort, there was no specific association with the progression of depression or anxiety in both cohorts [ 8 ].…”
Section: Genetic Factors Associated With Depression In Idiopathic Par...mentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to dopamine, MAO-B also degrades norepinephrine, which is implicated in several physiological functions, including cognition, pain, sleep, and emotional processing. Hence, MAO-B could mediate the pathophysiological mechanisms underlying the non-motor symptoms in PD, such as depression [ 8 ]. Recently, a study of PD patients from China and the Parkinson’s Progression Markers Initiative (PPMI) cohort has indicated that although the MAOB rs1799836 polymorphism was linked to the progression of non-motor symptoms of the patients in general in the Chinese cohort, there was no specific association with the progression of depression or anxiety in both cohorts [ 8 ].…”
Section: Genetic Factors Associated With Depression In Idiopathic Par...mentioning
confidence: 99%
“…Hence, MAO-B could mediate the pathophysiological mechanisms underlying the non-motor symptoms in PD, such as depression [ 8 ]. Recently, a study of PD patients from China and the Parkinson’s Progression Markers Initiative (PPMI) cohort has indicated that although the MAOB rs1799836 polymorphism was linked to the progression of non-motor symptoms of the patients in general in the Chinese cohort, there was no specific association with the progression of depression or anxiety in both cohorts [ 8 ]. Hence, the MAOA and MAOB gene polymorphisms seem not to significantly affect depression in PD patients.…”
Section: Genetic Factors Associated With Depression In Idiopathic Par...mentioning
confidence: 99%
See 2 more Smart Citations